Studies on the Arthropods and microorganisms of some Libyan Soils, Soil Arthropods and soil microorganisms of a Hill at El-Marj region - Kolkaila, A.A.; Hammad, S.M.; Abd-ElGhader, A.S.; Makawi, A.M. (The Libyan Journal of Agriculture, 2023)
SUMMARY The distribution of soil Arthropods and soil Microorganisms at different heights of a hill at El-Marj region was carried out. The base of the hill is 400 meters above the sea level and samples were taken 15 meters apart. Members of several classes of Arthropoda as well as members of orders Pro-tura and Thysanura were recorded here for the first time. Oribatid mites were dominating due to the high organic matter content. Number of Collembola were higher than in other tested samples of Lybian soils and increased with the moisture contents. There appeared a general trend of increase in the populations of both soil Arthropods and soil Microorganisms as height increased. Counts of Actinomycetes were higher than in other samples analysed previously.